Consumption pattern of milk products in Puri district of Odisha - Prusty, Suvashree R (Indian Journal of Dairy Science, 2017)
A study was conducted to analyse the consumption pattern of milk products in various categories of milk producer groups in Puri district of Odisha. The information is obtained in year 2016 from the stratified random sample of the consumers from two villages i.e. Sarbapada and Nuapada of Nimapada block. A Simple tabular analysis i.e. overall monthly expenditure on milk products was adopted to accomplish the objective. It was observed that various income, age and occupation group influence the consumption pattern effectively. On an average, monthly expenditure on milk products is Rs.300.16. The expenditure on curd was Rs. 126.00 (41.97%), on cheese Rs. 56.66 (18.87%), on paneer Rs. 86.66 (28.87%), on butter Rs.9.16 (3.05%), on lassi Rs.1.25 (0.41 %), on ghee Rs.20.41 (6.80%) i.e. highest on curd and lowest on lassi. The income group ≤ Rs.4000 are spending highest (44.05%) on curd and no expenditure on ghee, lassi and butter, The income group Rs. 4001-8000 spending highest on Curd (54.74%) and least on butter(0.6%) and The income group ≥ Rs. 8001 spending highest on paneer (42.2%), none on lassi. All age group i.e. 20-40, 41-60 and 61-80 preferred highest to curd and least to ghee and lassi. All the occupation group i.e. farming, service and business preferred curd and panner and least to ghee and lassi. Hence, curd is mostly proffered by all income, age and business groups which indicate that curd is most popular milk product in the study area.